Play it again – redundancy, literature and language games - Kula, Agnieszka; Skibski, Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The problem under consideration has its origin in the phenomenon of gameplay, which intersperses the rules and possible freedom of execution. The tensions between habit and surprise, regularity and irregularity created in this way expose the potential that lies in the grammatical conditions of the language use. The phenomenon of redundancy, considered in the context of a language game, can be presented in at least three ways: 1. redundancy as a non-game, 2. redundancy as a game – a struggle, 3. redundancy as a game – cooperation. In the latter approach, the recipient is invited to search for ambiguity, to take pleasure in activating non-obvious orders of literary expression. The article presents two very different examples of how redundancy functions in literary texts - a poem by Krystyna Miłobędzka and a short story by Janusz Rudnicki.